Reception of The Social and Political Dimensions in Baradouni's Poetry - Mahdi Yousef Mohammed alshawesh (Indonesian Journal of Arabic Studies, 2023)
Purpose: This research intends to investigate the social and political reception of Baradouni's poetry, which is renowned for its patriotism and is believed to contain values that represent the people, the nation, and the human conscience. Design/methods/approach: This study examines the historical reception of poet Abdullah Al-Bardouni's creative works using reception theory. analysis and description mechanisms in reception readings that reveal social and political implications, viz., critical products that greet Al-Baradouni's poetry in social and political aspects, and what social and political content and values are obtained from research and study, or which are neglected, then explaining what underlies the interaction of reception with the text in relation to meaning productivity, and resting on the method of facing and revealing. Findings: It is known that Baradouni's poetry contains a dimension of patriotism believed to contain values that represent the people, the nation, and the human conscience. In the national dimension, he focuses on Arab unity, the Palestinian issue, the independence of southern Yemen, the Iraqi revolution, Iraq's occupation of Kuwait, and Arab and Yemeni regional relations. While the social side includes social issues such as lineage pride, stratification discrimination, sectarianism, and women's issues related to family, revolution, marriage, divorce, widowhood, and moral deviation, it ignores social ills deserving of attention such as issues of vengeance, poverty, backwardness, disease, and ignorance.